UiTM: One stop data centre bot / Mohamad Ezad Hafez Mohd Pahroraji ... [et al.] - Mohd Pahroraji, Mohamad Ezad Hafez; Ayob, Mohd Asraf; Abu Bakar, Muhammad Fauzan; Saaid, Mohammad Nabil Fikri; Jasni, Mohd Dzuliqyan; Zulkifli, Mohd Zul Aswad (2022)
UiTM is a large organization with various units and departments. Each of the unit and department operates its own website to convey, manage and update system, information, calendar, forms, directory, circular and regulations. However, UiTM citizens such as staffs, academic advisors and students can become overwhelmed with the scattered websites throughout the UiTM internal system. At times, it is time consuming and exhausting to search for the required information due to the scattered websites all over the places. There were occasions in which UiTM citizens were not aware of such existence of a particular website of certain units or departments and some of them might have no clue of which website to source for forms download or information search. Therefore, a bot called ‘UiTM: One Stop Data Centre’ was developed using Telegram bot to overcome this problem. This bot is operated within the popular messaging app Telegram and free to use. With this bot, all UiTM system websites and other information are grouped, arranged and are accessible anytime and anywhere. Once the Telegram App was installed, the bot can be browsed, and used immediately. Since Telegram application can be installed in many devices such as mobile phone, tablet, and computer in various platforms such as Windows, Android, and iOS simultaneously with one account, this could be very helpful for UiTM citizens when they need to search for websites, download documents and retrieve information in just one stop data centre anytime anywhere without the need to google around vaguely.